2018
DOI: 10.1182/blood-2018-99-111954
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidities Are Frequent in Older Patients with De Novo Acute Lymphoblastic Leukemia (ALL) and Correlate with Induction Mortality: Analysis of More Than 1200 Patients from GMALL Data Bases

Abstract: Outcome of adult ALL has improved considerably during the past decades by intensive chemotherapy, which still remains a challenge in older pts. This may be partly due to comorbidities. So far there are no standards to differentiate pts who will be able to tolerate even age-adapted chemotherapy (fit vs unfit). In addition, little is known about the prevalence of comorbidities. Clinical trials with new compounds often represent a selection of pts w/o comorbidities. There is also no generally accepted tool for co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The 3-year OS for all elderly patients was 38%, with allo HCT increasing the 3-year OS to 87% with a leukemia-free survival of 75%, which was in the range of the outcome for younger transplanted and not transplanted adults. The intensive pediatric-inspired therapeutic regimen could be applied in EP in a high proportion of patients (65%) and was well tolerated with a low early death rate (6.7%) compared to historical rates of up to 35% depending on treatment selection and supportive therapy [17]. The low NRM and favorable outcome after allo HCT in general are most likely due to a combination of different factors such as a consequent supportive therapy including antimicrobial prophylaxis, individual selection of candidates, and consequent use of RIC in EP [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3-year OS for all elderly patients was 38%, with allo HCT increasing the 3-year OS to 87% with a leukemia-free survival of 75%, which was in the range of the outcome for younger transplanted and not transplanted adults. The intensive pediatric-inspired therapeutic regimen could be applied in EP in a high proportion of patients (65%) and was well tolerated with a low early death rate (6.7%) compared to historical rates of up to 35% depending on treatment selection and supportive therapy [17]. The low NRM and favorable outcome after allo HCT in general are most likely due to a combination of different factors such as a consequent supportive therapy including antimicrobial prophylaxis, individual selection of candidates, and consequent use of RIC in EP [18].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the exact prevalence and relative contribution of comorbidities in ALL patients and no guidelines exist for the distinction between unfit and fit EP who can tolerate age-adjusted chemotherapy at all. The German Multicenter Study Group for Adult ALL (GMALL) reported a comorbidity rate of 57-92% in patients above 55 years [17] with diabetes, vascular disease, and heart failure accounting for most comorbidities; prior malignancy was present in up to 22%. In our EP cohort, we found a similar comorbidity RIC reduced-intensity conditioning Table 3 (continued) distribution and rate (84%) but with a higher proportion of prior malignancy (42%).…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Survival rates are especially poor in older adult patients at approximately 20%. 21,23,24 Although the exact OS percentage can vary based on how the age range is defined for pediatric, AYA, and adult patients, the trend is nonetheless clear that OS decreases substantially with increased age. 21 The exception is infants younger than age 1, which is an age group that has not seen any improvement in survival over the last 30 years.…”
Section: Overviewmentioning
confidence: 99%
“…Relative to treatment outcomes in pediatric and young adult patients with ALL, prolonged survival rates for older adults, especially those aged .60 years, remain low at approximately 20%. [1][2][3] In Philadelphia chromosome (Ph)2positive ALL, however, the difference in overall survival (OS) and outcomes between older and younger patients is less than with Ph-negative ALL, due in part to the availability of well-tolerated, effective oral BCR-ABL1 tyrosine kinase inhibitor (TKI) therapy. [4][5][6][7][8][9][10] Current approaches to evaluating older adult patients with newly diagnosed ALL for treatment include assessment of leukemia genetics, fitness for therapy, and performance status.…”
Section: Overviewmentioning
confidence: 99%
“…11 However, these findings should not be interpreted as an indication to withhold intensive therapy, but rather stress the importance of tailoring therapy, as highlighted by the German Multicenter Study Group for Adult ALL (GMALL). 3 Unfortunately, older patients with newly diagnosed ALL often do not receive chemotherapy or bone marrow transplant, highlighting the need for guidance in this population. [14][15][16][17] Minimal/Measurable residual disease (MRD) after therapy in ALL refers to the presence of leukemic cells below the threshold of detection using conventional morphologic methods, and is a strong predictive factor of outcomes in ALL across all age groups.…”
Section: Overviewmentioning
confidence: 99%